THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDES OF ADOLESCENT FEMALE TOWARDS THE MEASURES OF PREVENTION OF LUCHING IN NAGORI RABUHIT, SUB-DISTRICT OF GUNUNG MALIGAS, DISTRICT SIMALUNGUN, 2016 - Yunardi (PT. Radja Intercontinental Publishing, 2021)
Based on the findings of the researchers that there were 5 young women in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency, experiencing vaginal discharge. This research was conducted to find out whether there is a relationship between the knowledge and attitudes of young women towards the prevention of vaginal discharge in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency in 2016. This type of research is descriptive with the population in this study being all young women in Nagori Rabuhit, Gunung Maligas District, Simalungun, namely as many as 108 people who were sampled as many as 85 people using the simple random sampling technique, which is a simple random sampling method. The results of this study the majority have knowledge.